Optimization of cooperative production schemes based on incentive mechanisms in an agro-business model (2018)
"Efficient and fair agriculture is key to food security, sustainable growth and poverty reduction in developing countries. This research addresses decision processes in a multi-agent agro-industrial problem in the context of the Colombian post-war development. The challenge is to design production schemes that account for the individual interests of farmers, the shared interest of the farmer's cooperative, and the efficiency of the overall supply chain, considering prices that depend on production levels, which lead to a need for efficient coordination. We propose an optimization-based methodology, in which Mixed Integer Linear Programming (MILP) models are implemented to: first, satisfy scenarios that pursue individual farmer's interests (i.e., maximizing profits); second, design incentive schemes that exploit efficiency to incentivize farmers to adopt collectively beneficial policies without deterring individual benefits; third, include logistic cost savings due to cooperative work."-- Tomado del Formato de Documento de Grado